Thermal Stability and Reliability Test of Some Saturated Fatty Acids for Low and Medium Temperature Thermal Energy Storage - Abhishek Anand; Karunesh Kant; Amritanshu Shukla; Chang-Ren Chen; Atul Sharma (Energies, 2021)
Phase change materials have been overwhelmingly used for thermal energy storage applications. Among organics, fatty acids are an important constituent of latent heat storage. Most of the saturated fatty acid PCMs so far studied are either unary or binary constituents of pure fatty acids. In the present study, ternary blends of saturated fatty acids i.e., capric, lauric, myristic, stearic, and palmitic acids have been developed with different weight proportions. A series of 28 ternary blends viz. CA-LA-MA, CA-LA-PA, CA-LA-SA, CA-MA-PA, CA-MA-SA, and CA-PA-SA were prepared and analyzed with differential scanning calorimetry, thermal gravimetric analysis, and Fourier transform infrared spectroscopy. DSC analysis revealed that the prepared materials lie in the 15–30 °C temperature range. Also, 300 thermal melt/freeze cycles were conducted which showed ±10% variation in terms of the melting peak for most of the PCMs, with the average latent heat of fusion between 130 and 170 kJ/kg. The TGA analysis showed that most of the PCMs are thermally stable up to 100 °C and useful for medium-low storage applications, and FTIR analysis showed that the materials are chemically stable after repeated thermal cycles. Based on cycle test performances, the developed materials were found to be reliable for long-term use in building and photovoltaic applications.